Do Malaysian banks manage earnings through loan loss provisions? / Abd. Ghafar Ismail, Roselee Shah Shaharudin and Ananda R. Samudhram - Ismail, Abd. Ghafar; Shaharudin, Roselee Shah; R. Samudhram, Ananda (Faculty of Accountancy, 2005)
The 1988 Basle regulations are meant to synchronise banking regulations worldwide and add to the stability of the global banking system. Basle II, due to be released in 2006, addresses some of the flaws in the 1988 accord. However, both versions do not close a loophole for managing earnings through discretionary adjustments of the loan loss provisions. Some researchers have found indications of income smoothing through loan loss provisions in banks, but others have concluded otherwise. All of these studies were conducted on banks outside of Malaysia. This study looks specifically at Malaysian banks, and uses a model based on bank-specific and macroeconomic factors that are peculiar to Malaysia. It concludes that Malaysian banks do not smoothen income. The likely reason is that good governance in Malaysian banks is driven more by regulatory measures imposed by the authorities than stock market discipline. Thus bankers do not seem to be concerned with managing earnings to present a rosy picture to investors. However, from a macroeconomic perspective, stacking up loan loss provisions during good times will help to release more credit during downturns in economic cycles, helping to soften the impact of recessions. Further research on whether Malaysian banks conduct capital management, to meet regulatory capital requirements, will help to shed more light on the behaviour of Malaysian banks.